The OECD model convention, 1996 and beyond : proceedings of a seminar held in Geneva in 1996 during the 50th Congress of the International Fiscal Association /: proceedings of a seminar held in Geneva in 1996 during the 50th Congress of the International Fiscal Association. (2016) - Unknown
No abstract available